Coated electric wire and method for manufacturing coated electric wire

By adopting a three-layer structure coated wire, using a coating composition with a polymer compound having an amide group and an imide group and a fluorine-containing polymer compound, the problem of floating or wrinkling during bending is solved, and the effect of low relative dielectric constant and high local discharge starting voltage is achieved.

CN119816904APending Publication Date: 2025-04-11DAIKIN INDUSTRIES LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380062335.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-29
Filing Date
2023-08-02
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing coated wires are prone to floating or wrinkle when bending, and it is difficult to achieve both low relative dielectric constant and high local discharge starting voltage.

Method used

The coated wire with a three-layer structure is adopted, wherein the first layer is formed of a liquid coating composition of a polymer compound having an amide group and an imide group, the second layer is formed of a liquid or powder coating composition of a polymer compound and a fluorine-containing polymer compound, and the third layer is formed by extrusion molding of a fluorine-containing polymer compound.

Benefits of technology

It is realized that the coated wire is not prone to wrinkles when bending, and has a low relative dielectric constant and a high local discharge starting voltage, which improves the adhesion strength between the flat wire base material and the coating layer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005287626510000151
    Figure BDA0005287626510000151
  • Figure BDA0005287626510000211
    Figure BDA0005287626510000211
  • Figure BDA0005287626510000261
    Figure BDA0005287626510000261
Patent Text Reader

Abstract

Provided is a coated electric wire comprising a flat electric wire base material and a coating layer formed on the outer periphery of the flat electric wire base material, the coating layer comprising: a first layer formed from a liquid coating composition (1) containing a polymer compound (1) having an amide group and / or an imide group, and a second layer formed from a liquid coating composition (2) containing a polymer compound (3) having an amide group and / or an imide group; a second layer formed from a liquid coating composition (2) containing a polymer compound (2) having an amide group and / or an imide group and a fluorine-containing polymer compound (2), or a powder coating composition (2) containing a polymer compound (2) having an amide group and / or an imide group and a fluorine-containing polymer compound (2); and a third layer formed by extrusion molding of a fluorine-containing polymer compound (3).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a covered electric wire and a method for producing the covered electric wire. Background Art

[0002] Patent document 1 describes an electric wire, characterized in that it has a conductor and a first insulating layer formed on the outer periphery of the conductor, the first insulating layer is composed of a thermosetting resin and a fluororesin, the mass ratio of the thermosetting resin to the fluororesin is 90:10 to 10:90, and the first insulating layer is a layer formed by mixing a thermosetting resin solution with a fluororesin organic sol and applying the obtained mixed solution on the conductor and baking it.

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: International Publication No. 2011 / 024809 Summary of the invention

[0006] Problems to be solved by the invention

[0007] An object of the present disclosure is to provide a covered electric wire having a low relative dielectric constant and a high partial discharge inception voltage, wherein wrinkles are unlikely to occur in the covering layer even when bent, and wherein the adhesion strength between a flat electric wire base material and the covering layer is high.

[0008] Means for solving problems

[0009] According to the present disclosure, a covered electric wire is provided, which is a covered electric wire comprising a flat electric wire base material and a covering layer formed on the outer periphery of the flat electric wire base material, wherein the covering layer comprises: a first layer formed from a liquid coating composition (1) comprising a polymer compound (1) having either or both of an amide group and an imide group; a second layer formed from a liquid coating composition (2) comprising a polymer compound (2) having either or both of an amide group and an imide group and a fluorine-containing polymer compound (2), or a powder coating composition (2) comprising a polymer compound (2) having either or both of an amide group and an imide group and a fluorine-containing polymer compound (2); and a third layer formed by extrusion molding of the fluorine-containing polymer compound (3).

[0010] Effects of the Invention

[0011] According to the present disclosure, it is possible to provide a covered electric wire having a low relative dielectric constant and a high partial discharge inception voltage, wherein wrinkles are unlikely to occur in the covering layer even when bent, and having high adhesion strength between a rectangular electric wire base material and the covering layer. DETAILED DESCRIPTION

[0012] Hereinafter, specific embodiments of the present disclosure will be described in detail, but the present disclosure is not limited to the following embodiments.

[0013] The covered electric wire of the present disclosure includes a rectangular electric wire base material and a covering layer formed on the outer periphery of the rectangular electric wire base material.

[0014] Fluorinated polymer compounds have non-adhesive properties, so when a coating layer containing a fluorinated polymer compound is provided on a flat wire substrate of a covered electric wire, there is a problem that the flat wire substrate and the coating layer cannot be adhered to each other with sufficient strength. Therefore, when the conventional covered electric wire is bent or folded, there is a problem that the coating layer floats from the flat wire substrate or wrinkles are generated in the coating layer.

[0015] On the other hand, if the coating layer is formed of a material that is easily adhered to the rectangular wire substrate, the relative dielectric constant of the coating layer of the coated wire increases, or the partial discharge inception voltage of the coated wire decreases, which makes it difficult to obtain a coated wire with excellent electrical performance.

[0016] The covered electric wire disclosed in the present invention is obtained by appropriately combining the constituent materials and the forming method of the three layers. Therefore, the covered electric wire disclosed in the present invention has a low relative dielectric constant and a high partial discharge inception voltage, and wrinkles are not easily generated in the covering layer even when bent, and the flat electric wire base material and the covering layer are closely bonded with high bonding strength.

[0017] (Flat wire base material)

[0018] The shape of the flat wire substrate is not particularly limited as long as it is a flat wire having a substantially rectangular cross section. The corners of the cross section of the flat wire substrate may be right angles or may have rounded corners. In addition, the flat wire substrate may be a single wire, a group of wires, a stranded wire, etc., if the overall cross section of the flat wire substrate is substantially rectangular, but a single wire is preferred.

[0019] The flat electric wire substrate is not particularly limited as long as it is made of a conductive material, and can be made of copper, copper alloy, aluminum, aluminum alloy, iron, silver, nickel, etc., preferably copper, copper alloy, aluminum or aluminum alloy. In addition, a flat electric wire substrate plated with silver plating, nickel plating, etc. can also be used. As copper, oxygen-free copper, low-oxygen copper, copper alloy, etc. can be used.

[0020] The width of the cross section of the flat wire substrate may be 1 mm to 75 mm, and the thickness of the cross section of the flat wire substrate may be 0.1 mm to 30 mm. The outer diameter of the flat wire substrate may be 6.5 mm or more and 200 mm or less. In addition, the ratio of the width to the thickness may be greater than 1 and less than 30.

[0021] From the viewpoint of more firmly adhering the rectangular wire substrate and the covering layer, the surface roughness Sz of the rectangular wire substrate is preferably 0.2 μm to 12 μm, more preferably 1 μm or more, further preferably 5 μm or more, and more preferably 10 μm or less.

[0022] The surface roughness of the flat wire substrate can be adjusted by surface treatment of the flat wire substrate using a surface treatment method such as etching, sandblasting, laser treatment, etc. In addition, it is also possible to set concavities and convexities on the surface of the flat wire substrate by surface treatment. The smaller the distance between the concavities and convexities, the better, for example, 5 μm or less. In addition, regarding the size of the concavities and convexities, for example, the area of ​​each concave portion when the convex portion relative to the unprocessed surface is cut is 1 μm. 2 The concavoconvex shape may be a single concavoconvex shape of a crater, or may be branched into an ant's nest shape.

[0023] (Coating layer)

[0024] The covered electric wire of the present disclosure includes a covering layer formed on the outer periphery of a flat electric wire base material, and the covering layer includes a first layer, a second layer, and a third layer. In the covered electric wire of the present disclosure, usually, the first layer is formed on the outer periphery of the flat electric wire base material, the second layer is formed on the outer periphery of the first layer, and the third layer is formed on the outer periphery of the second layer.

[0025] The first layer and the second layer are both coating films formed from coating compositions. The first layer is a coating film formed from a liquid coating composition (1). The second layer is a coating film formed from a liquid coating composition (2) or a powder coating composition (2).

[0026] The liquid coating composition contains a polymer compound or a fluorinated polymer compound and a solvent. The powder coating composition contains a powder of a polymer compound or a fluorinated polymer compound. In the present disclosure, the term "powder coating composition" is used when the powder coating contains only a powder of a polymer compound or only a powder of a fluorinated polymer compound, that is, when the powder coating does not contain multiple components.

[0027] The third layer is an extrudate formed by an extrusion molding method from a fluorinated polymer compound (3) or an extrusion molding composition containing a fluorinated polymer compound (3) and other components. The extrudate can easily form a layer having a thickness greater than that of the coating film. For example, the thickness of the extrudate (third layer) may be 90 μm or more, and the thickness of the coating film (first layer or second layer) may be less than 90 μm.

[0028] The liquid coating composition (1) contains a polymer compound (1) having either or both of an amide group and an imide group. By applying the liquid coating composition (1) to the outer periphery of a rectangular electric wire substrate to form a first layer, the first layer can be formed to be in close contact with the rectangular electric wire substrate with high adhesion strength, thereby forming a coating layer that is in close contact with the rectangular electric wire substrate with high adhesion strength and that is less likely to wrinkle even when bent.

[0029] The liquid coating composition (2) comprises a polymer compound (2) having either or both of an amide group and an imide group, and a fluorine-containing polymer compound (2). The second layer is formed by applying the liquid coating composition (2) to the periphery of the first layer, and the second layer can be sufficiently adhered to the first layer and the third layer without impairing the low relative dielectric constant and high partial discharge inception voltage of the coating layer, thereby forming the second layer that provides the coating layer with excellent interlayer strength.

[0030] The powder coating composition (2) comprises a polymer compound (2) having either or both of an amide group and an imide group, and a fluorine-containing polymer compound (2). The second layer is formed by applying the powder coating composition (2) to the periphery of the first layer, and the second layer can be sufficiently adhered to the first layer and the third layer without impairing the low relative dielectric constant and high partial discharge inception voltage of the coating layer, thereby forming the second layer that provides the coating layer with excellent interlayer strength.

[0031] The third layer contains a fluorinated polymer compound (3). By forming the third layer using an extrudate of the fluorinated polymer compound (3) on the periphery of the second layer, a low relative dielectric constant and a high partial discharge inception voltage can be imparted to the coating layer, and the third layer can be sufficiently adhered to the second layer, thereby forming a coating layer having excellent interlayer strength.

[0032] From the perspective of insulation properties, the thickness of the coating layer is preferably 30 μm to 500 μm, more preferably 60 μm or more, further preferably 90 μm or more, further preferably 120 μm or more, more preferably 400 μm or less, further preferably 300 μm or less, further preferably 250 μm or less. If the thickness is too large, when the coated wire is used in a device such as a motor, miniaturization of the device may become difficult, and if the thickness is too small, sufficient insulation may not be obtained.

[0033] From the perspective of making the rectangular wire substrate and the covering layer sufficiently close to each other and forming a covering layer that is less likely to wrinkle even when bent, the thickness of the first layer is preferably 1 μm to 50 μm, more preferably 3 μm or more, further preferably 6 μm or more, more preferably 40 μm or less, further preferably 20 μm or less, and further preferably 10 μm or less.

[0034] From the perspective of ensuring that the second layer is in full contact with the first and third layers without damaging the low relative dielectric constant and high local discharge inception voltage of the coating layer, the thickness of the second layer is preferably 5 μm to 100 μm, more preferably greater than 10 μm, more preferably less than 60 μm, further preferably less than 40 μm, and further preferably less than 30 μm.

[0035] From the perspective of imparting a low relative dielectric constant and a high local discharge starting voltage to the coating layer and making the third layer sufficiently close to the second layer, the thickness of the third layer is preferably 25 μm to 400 μm, more preferably 50 μm or more, further preferably 75 μm or more, further preferably 90 μm or more, more preferably 300 μm or less, further preferably 250 μm or less.

[0036] The relative dielectric constant of the coating layer is preferably 2.1 to 2.8, more preferably 2.6 or less, and further preferably 2.5 or less. The coated electric wire disclosed herein is formed by appropriately combining constituent materials and formation methods of three layers, and thus the relative dielectric constant of the coating layer can be reduced.

[0037] The partial discharge inception voltage of the coating layer is preferably 1000 (Vp) to 2100 (Vp), more preferably 1500 (Vp) or more, further preferably 1700 (Vp) or more, and further preferably 1900 (Vp) or more. The coated electric wire disclosed in the present invention is formed by appropriately combining the constituent materials and formation methods of the three layers, so the partial discharge inception voltage of the coating layer can be increased.

[0038] The partial discharge inception voltage of the coating layer preferably satisfies the following formula: The coated electric wire disclosed in the present invention is formed by appropriately combining the constituent materials and formation methods of the three layers, and thus the partial discharge inception voltage can be increased.

[0039] Partial discharge starting voltage (Vp) ≥ 7.2 × t + 880

[0040] (t: thickness of the above coating layer (μm))

[0041] The covering layer may further include other layers as long as it includes the first layer, the second layer, and the third layer. However, a covered electric wire that exhibits a desired effect can be obtained even without including other layers.

[0042] (1st floor)

[0043] The first layer is formed from a liquid coating composition (1) containing a polymer compound (1) having either or both an amide group and an imide group. The liquid coating composition (1) may contain only a polymer compound (1) having either or both an amide group and an imide group as the polymer compound.

[0044] In addition to the polymer compound (1), the liquid coating composition (1) may further contain a solvent. Examples of the solvent include water and organic solvents, and organic solvents are preferred. Examples of the organic solvent include N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, N-butyl-2-pyrrolidone, 3-methoxy-N,N-dimethylpropionamide, N,N-dimethylacetamide, N,N-dimethylformamide, cresol, methyl isobutyl ketone, and the like.

[0045] From the viewpoint of being able to easily form a layer having a desired thickness, the viscosity of the liquid coating composition (1) is preferably 10 (cP) to 10000 (cP), more preferably 50 (cP) or more, further preferably 100 (cP) or more, more preferably 1000 (cP) or less, further preferably 500 (cP) or less. The viscosity of the liquid coating composition (1) can be adjusted by adjusting the content of the polymer compound (1) in the liquid coating composition (1).

[0046] The content of the polymer compound (1) in the liquid coating composition (1) is preferably 1 to 50% by weight, more preferably 10% by weight or more, and more preferably 40% by weight or less, based on the mass of the liquid coating composition (1).

[0047] Liquid coating composition (1) can include other components as needed. As other components, crosslinking agent, antistatic agent, heat stabilizer, foaming agent, foaming nucleating agent, antioxidant, surfactant, photopolymerization initiator, anti-wear agent, surface modifier, various pigments of organic / inorganic system, copper poison inhibitor, bubble prevention agent, close fit imparting agent, lubricant, processing aid, colorant, phosphorus stabilizer, lubricant, release agent, sliding material, ultraviolet absorber, dye pigment, reinforcing material, anti-drip agent, filling material, curing agent, ultraviolet curing agent, flame retardant and other additives can be cited. As the content of other components in liquid coating composition (1), relative to the mass of polymer compound (1) in liquid coating composition (1), preferably less than 30% by weight, more preferably less than 10% by weight, more preferably less than 5% by weight, the lower limit is not particularly limited, and can be more than 0% by weight. That is, liquid coating composition (1) may not contain other components.

[0048] (Layer 2)

[0049] The second layer is formed from a liquid coating composition (2) or a powder coating composition (2).

[0050] The liquid coating composition (2) contains a polymer compound (2) having either or both of an amide group and an imide group, and a fluorine-containing polymer compound (2). The liquid coating composition (2) may contain only the polymer compound (2) having either or both of an amide group and an imide group and the fluorine-containing polymer compound (2) as polymer compounds.

[0051] In addition to the polymer compound (2) and the fluorine-containing polymer compound (2), the liquid coating composition (2) may further contain a solvent. Examples of the solvent include water and an organic solvent. Examples of the organic solvent include N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, N-butyl-2-pyrrolidone, 3-methoxy-N,N-dimethylpropionamide, N,N-dimethylacetamide, N,N-dimethylformamide, cresol, methyl isobutyl ketone, and the like.

[0052] From the viewpoint of being able to easily form a layer having a desired thickness, the viscosity of the liquid coating composition (2) is preferably 10 (cP) to 10000 (cP), more preferably 50 (cP) or more, further preferably 100 (cP) or more, more preferably 1000 (cP) or less, further preferably 500 (cP) or less. The viscosity of the liquid coating composition (2) can be adjusted by adjusting the content of the polymer compound (2) and the fluorine-containing polymer compound (2) in the liquid coating composition (2).

[0053] The content of the polymer compound (2) and the fluorine-containing polymer compound (2) in the liquid coating composition (2) is preferably 1% to 90% by weight, more preferably 10% by weight or more, and more preferably 80% by weight or less, based on the mass of the liquid coating composition (2).

[0054] The powder coating composition (2) comprises a polymer compound (2) having either or both of an amide group and an imide group, and a fluorine-containing polymer compound (2). The polymer compound (2) and the fluorine-containing polymer compound (2) in the powder coating composition (2) are usually both powders. The powder coating composition (2) may comprise only the polymer compound (2) having either or both of an amide group and an imide group and the fluorine-containing polymer compound (2) as polymer compounds.

[0055] From the perspective of being able to easily form a layer having a desired thickness, the average particle size of the powder coating composition (2) is preferably 1 (μm) to 100 (μm), more preferably 5 μm or more, further preferably 10 μm or more, more preferably 90 μm or less, further preferably 80 μm or less.

[0056] In the liquid coating composition (2) or the powder coating composition (2), from the perspective of allowing the second layer to be fully in close contact with the first layer and the third layer without damaging the low relative dielectric constant and high local discharge inception voltage of the coating layer, the volume ratio of the polymer compound (2) to the fluorine-containing polymer compound (2) is preferably 10 / 90 to 90 / 10, more preferably 15 / 85 or more, and more preferably 85 / 15 or less.

[0057] The liquid coating composition (2) or the powder coating composition (2) may contain other components as required. As other components, crosslinking agents, antistatic agents, heat stabilizers, foaming agents, foaming nucleating agents, antioxidants, surfactants, photopolymerization initiators, anti-wear agents, surface modifiers, various pigments of organic / inorganic systems, copper poison inhibitors, bubble preventers, adhesion imparting agents, lubricants, processing aids, colorants, phosphorus stabilizers, lubricants, mold release agents, sliding materials, ultraviolet absorbers, dye pigments, reinforcing materials, anti-drip agents, filling materials, curing agents, ultraviolet curing agents, flame retardants and other additives can be cited. As the content of other components in the liquid coating composition (2) or the powder coating composition (2), relative to the mass of the polymer compound (2) and the fluorine-containing polymer compound (2) in the liquid coating composition (2) or the powder coating composition (2), preferably less than 30% by weight, more preferably less than 10% by weight, and further preferably less than 5% by weight, the lower limit is not particularly limited, and can be more than 0% by weight. That is, the liquid coating composition (2) or the powder coating composition (2) may not contain other components.

[0058] (Layer 3)

[0059] The third layer is formed by extrusion molding of the fluorinated polymer compound (3). The fluorinated polymer compound (3) will be described in detail later.

[0060] The third layer may contain other ingredients as needed. As other ingredients, crosslinking agents, antistatic agents, heat stabilizers, foaming agents, foaming nucleating agents, antioxidants, surfactants, photopolymerization initiators, anti-wear agents, surface modifiers, various pigments of organic / inorganic systems, copper poison inhibitors, bubble preventers, adhesion imparting agents, lubricants, processing aids, colorants, phosphorus stabilizers, lubricants, mold release agents, sliding materials, ultraviolet absorbers, dye pigments, reinforcing materials, anti-drip agents, filling materials, curing agents, ultraviolet curing agents, flame retardants and other additives may be cited. As the content of other ingredients in the third layer, relative to the mass of the fluorine-containing polymer compound (3) in the third layer, it is preferably less than 30% by weight, more preferably less than 10% by weight, and further preferably less than 5% by weight, and the lower limit is not particularly limited, and can be more than 0% by weight. That is, the third layer may not contain other ingredients.

[0061] (Polymer Compounds)

[0062] Next, the polymer compound used for the covering layer of the covered electric wire is described. The polymer compound described below can be suitably used as the polymer compound (1) forming the first layer and the polymer compound (2) forming the second layer.

[0063] In the present disclosure, a "polymer compound" has either or both of an amide group and an imide group, and preferably has no fluorine atom. The polymer compound may have an amide group (amide bond) or an imide group (imide bond) in the main chain or side chain of the polymer compound.

[0064] As the polymer compound, from the aspect of the close adhesion with the flat wire substrate or the close adhesion with other layers, it is preferred to select at least one of the group consisting of polyamideimide, polyetherimide, polyimide and thermoplastic polyimide, and more preferably at least one of the group consisting of polyamideimide and polyimide. In addition, as the polymer compound, two or more polymer compounds may be used in combination. For example, as the polymer compound, a combination of polyamideimide and polyimide may be used.

[0065] Polyamideimide is a resin composed of a polymer having an amide bond and an imide bond in the molecular structure. As polyamideimide, there is no particular limitation, and examples thereof include: a resin composed of a high molecular weight polymer obtained by the reaction of an aromatic diamine having an amide bond in the molecule with an aromatic tetracarboxylic acid such as pyromellitic acid; a reaction of an aromatic tricarboxylic acid such as trimellitic anhydride with a diamine such as 4,4-diaminophenyl ether or a diisocyanate such as diphenylmethane diisocyanate; a reaction of a dibasic acid having an aromatic imide ring in the molecule with a diamine, etc. As polyamideimide, it is preferably composed of a polymer having an aromatic ring in the main chain.

[0066] Polyimide is a resin composed of a polymer having an imide bond in the molecular structure. As polyimide, there is no particular limitation, and examples thereof include resins formed by high molecular weight polymers obtained by reaction of aromatic tetracarboxylic anhydrides such as pyromellitic anhydride, etc. As polyimide, it is preferably composed of a polymer having an aromatic ring in the main chain.

[0067] (Fluorinated polymer compounds)

[0068] Next, the fluorinated polymer compound used for the covering layer of the covered electric wire is described. The fluorinated polymer compound described below can be suitably used as the fluorinated polymer compound (2) forming the second layer and the fluorinated polymer compound (3) forming the third layer.

[0069] The fluorine-containing polymer compound is a polymer compound having fluorine atoms. The fluorine-containing polymer compound is generally a polymer compound in which hydrogen atoms bonded to carbon atoms constituting the main chain are partially or completely replaced by fluorine atoms.

[0070] As the fluorine-containing polymer compound, a perfluorinated polymer compound is preferred from the viewpoint of obtaining a coating layer showing a lower relative dielectric constant and a higher partial discharge inception voltage. In the present disclosure, a perfluorinated polymer compound refers to a polymer compound in which the content of perfluorinated monomer units relative to all polymerized units constituting the polymer compound is 90 mol % or more.

[0071] In the present disclosure, a perfluoromonomer refers to a monomer that does not contain a carbon atom-hydrogen atom bond in the molecule. A perfluoromonomer may also be a monomer in which some of the fluorine atoms bonded to carbon atoms are replaced by chlorine atoms in addition to carbon atoms and fluorine atoms, and may also have nitrogen atoms, oxygen atoms, sulfur atoms, phosphorus atoms, boron atoms or silicon atoms in addition to carbon atoms. As a perfluoromonomer, a monomer in which all hydrogen atoms are replaced by fluorine atoms is preferred.

[0072] From the perspective of obtaining a coating layer showing a lower relative dielectric constant and a higher partial discharge inception voltage, the relative dielectric constant of the fluorinated polymer compound is preferably 2.0 to 2.2, more preferably 2.1 or less. The relative dielectric constant of the fluorinated polymer compound can be measured at 23°C ± 2°C, relative humidity 50%, and frequency 1 kHz in accordance with JIS-C-2138.

[0073] As the fluorine-containing polymer compound, a fluororesin is preferred. In the present disclosure, a fluororesin refers to a partially crystalline fluoropolymer, which is a fluoroplastic. A fluororesin has a melting point and thermoplasticity, and can be melt-processable or non-melt-processable.

[0074] Examples of the fluororesin include polytetrafluoroethylene, tetrafluoroethylene (TFE) / fluoroalkyl vinyl ether (FAVE) copolymers, tetrafluoroethylene (TFE) / hexafluoropropylene (HFP) copolymers, TFE / FAVE / HFP copolymers, TFE / ethylene copolymers [ETFE], TFE / ethylene / HFP copolymers, ethylene / chlorotrifluoroethylene (CTFE) copolymers [ECTFE], polychlorotrifluoroethylene [PCTFE], CTFE / TFE copolymers, polyvinylidene fluoride [PVdF], TFE / vinylidene fluoride (VdF) copolymers [VT], polyvinyl fluoride [PVF], TFE / VdF / CTFE copolymers [VTC], and TFE / HFP / VdF copolymers.

[0075] Among them, the fluororesin is preferably at least one selected from the group consisting of polytetrafluoroethylene, TFE / FAVE copolymer, TFE / HFP copolymer and TFE / FAVE / HFP copolymer.

[0076] The polytetrafluoroethylene (PTFE) may be either non-melt-processable PTFE or melt-processable PTFE, but non-melt-processable PTFE is preferred.

[0077] Non-melt-processable PTFE generally has stretchability, fibrillation characteristics, and non-melt secondary processability. Non-melt secondary processability refers to the property that the melt flow rate cannot be measured at a temperature higher than the crystallization melting point according to ASTM D 1238 and D 2116, that is, the property that it is not easy to flow even in the melting temperature range.

[0078] PTFE can be tetrafluoroethylene (TFE) homopolymer, or it can be modified PTFE containing TFE unit and modified monomer unit. In the present disclosure, "modified PTFE" refers to a material obtained by copolymerizing a small amount of comonomer and TFE without imparting melt processability to the obtained copolymer. As comonomer, it is not particularly limited, and examples thereof include hexafluoropropylene [HFP], chlorotrifluoroethylene [CTFE], perfluoro (alkyl vinyl ether) [PAVE], etc. The ratio of comonomer addition to modified PTFE is different according to its type, for example, relative to the total mass of TFE and a small amount of comonomer, preferably 0.001 mass % to 1 mass %. In the present disclosure, the content of each monomer unit constituting PTFE can be calculated by appropriately combining NMR, FT-IR, elemental analysis, and fluorescent X-ray analysis according to the type of monomer.

[0079] The standard specific gravity (SSG) of PTFE is preferably 2.280 or less, more preferably 2.210 or less, further preferably 2.200 or less, and preferably 2.130 or more. SSG can be measured by the water displacement method according to ASTM D 792 using a sample molded according to ASTM D 4895-89.

[0080] The peak temperature of PTFE is preferably in the range of 333° C. to 347° C. More preferably, it is 335° C. or higher and 345° C. or lower. The peak temperature is the temperature corresponding to the maximum value in the heat of fusion curve when the temperature of PTFE that has not been heated to a temperature of 300° C. or higher is increased at a rate of 10° C. / min using a differential scanning calorimeter [DSC].

[0081] As the fluorinated polymer compound, a melt-processable fluorinated polymer compound may be used. In particular, from the perspective of being able to easily form a layer having a desired thickness, it is preferred to use a melt-processable fluorinated polymer compound as the fluorinated polymer compound (3) for forming the third layer. In addition, from the perspective of being able to easily form a layer having a desired thickness, it is preferred to use a melt-processable fluorinated polymer compound as the fluorinated polymer compound (2) contained in the powder coating composition (2) for forming the second layer.

[0082] In the present disclosure, melt processability means that the polymer can be melted and processed using existing processing equipment such as extruders and injection molding machines. Therefore, the melt flow rate of the melt-processable fluorinated polymer compound is usually 0.01 g / 10 min to 500 g / 10 min.

[0083] The melt flow rate of the fluorinated polymer compound is preferably 0.1 to 100 g / 10 min, more preferably 80 g / 10 min or less, further preferably 70 g / 10 min or less, and preferably 5 g / 10 min or more, more preferably 10 g / 10 min or more.

[0084] The melt flow rate of the fluorinated polymer compound is a value obtained as the mass (g / 10 minutes) of the polymer flowing out from a nozzle having an inner diameter of 2.1 mm and a length of 8 mm at 372°C and a load of 5 kg per 10 minutes using a melt flow indexer (manufactured by Yasuda Seiki Co., Ltd.) in accordance with ASTM D1238.

[0085] The melting point of the fluorine-containing polymer compound is preferably 200°C to 322°C, more preferably 230°C or higher, further preferably 250°C or higher, and more preferably 320°C or lower.

[0086] The melting point can be determined using a differential scanning calorimeter [DSC].

[0087] As the melt-processable fluorine-containing polymer compound, a melt-processable fluororesin is preferred. Examples of melt-processable fluororesins include tetrafluoroethylene (TFE) / fluoroalkyl vinyl ether (FAVE) copolymers, tetrafluoroethylene (TFE) / hexafluoropropylene (HFP) copolymers, TFE / FAVE / HFP copolymers, TFE / ethylene copolymers [ETFE], TFE / ethylene / HFP copolymers, ethylene / chlorotrifluoroethylene (CTFE) copolymers [ECTFE], polychlorotrifluoroethylene [PCTFE], CTFE / TFE copolymers, polyvinylidene fluoride [PVdF], TFE / vinylidene fluoride (VdF) copolymers [VT], polyvinyl fluoride [PVF], TFE / VdF / CTFE copolymers [VTC], and TFE / HFP / VdF copolymers.

[0088] As the melt-processable fluororesin, at least one selected from the group consisting of TFE / FAVE copolymers, TFE / HFP copolymers and TFE / FAVE / HFP copolymers is preferred.

[0089] TFE / FAVE copolymer is a copolymer containing tetrafluoroethylene (TFE) units and fluoroalkyl vinyl ether (FAVE) units.

[0090] Examples of FAVE constituting the FAVE unit include those selected from the group consisting of the following general formula (1):

[0091] CF2=CFO(CF2CFY 1 O) p -(CF2CF2CF2O) q -Rf (1)

[0092] (Where Y 1 represents F or CF3, Rf represents a perfluoroalkyl group having 1 to 5 carbon atoms, p represents an integer of 0 to 5, and q represents an integer of 0 to 5. ) and the general formula (2):

[0093] CFX=CXOCF2OR 1 (2)

[0094] (wherein, X is the same or different and represents H, F or CF3, R 1 It represents a linear or branched fluoroalkyl group having 1 to 6 carbon atoms which may contain 1 to 2 atoms of at least one kind selected from the group consisting of H, Cl, Br and I, or a cyclic fluoroalkyl group having 5 or 6 carbon atoms which may contain 1 to 2 atoms of at least one kind selected from the group consisting of H, Cl, Br and I. At least one of the group consisting of monomers represented by ).

[0095] As FAVE, the monomer represented by the general formula (1) is preferred, more preferably at least one selected from the group consisting of perfluoro(methyl vinyl ether), perfluoro(ethyl vinyl ether) (PEVE) and perfluoro(propyl vinyl ether) (PPVE), further preferably at least one selected from the group consisting of PEVE and PPVE, and particularly preferably PPVE.

[0096] The content of the FAVE unit in the TFE / FAVE copolymer is preferably 1.0 mol% to 30.0 mol% relative to all monomer units, more preferably 1.2 mol% or more, further preferably 1.4 mol% or more, further preferably 1.6 mol% or more, particularly preferably 1.8 mol% or more, more preferably 3.5 mol% or less, further preferably 3.2 mol% or less, further preferably 2.9 mol% or less, particularly preferably 2.6 mol% or less.

[0097] The content of TFE units in the TFE / FAVE copolymer is preferably 99.0 mol% to 70.0 mol% relative to all monomer units, more preferably 96.5 mol% or more, further preferably 96.8 mol% or more, further preferably 97.1 mol% or more, particularly preferably 97.4 mol% or more, more preferably 98.8 mol% or less, further preferably 98.6 mol% or less, further preferably 98.4 mol% or less, particularly preferably 98.2 mol% or less.

[0098] In the present disclosure, the content of each monomer unit in the copolymer is expressed by 19 Determined by F-NMR method.

[0099] The TFE / FAVE copolymer may also contain monomer units from monomers copolymerizable with TFE and FAVE. In this case, the content of the monomers copolymerizable with TFE and FAVE is preferably 0 to 29.0 mol%, more preferably 0.1 mol% to 5.0 mol%, and further preferably 0.1 mol% to 1.0 mol%, relative to all monomer units of the TFE / FAVE copolymer.

[0100] Examples of monomers copolymerizable with TFE and FAVE include HFP, CZ 1 Z 2 =CZ 3 (CF2) n Z 4 (Where Z 1 , Z 2 and Z 3 Same or different, means H or F, Z 4 represents H, F or Cl, n represents an integer of 2 to 10) and CF2=CF-OCH2-Rf 1 (Where Rf 1 An alkyl perfluorovinyl ether derivative represented by (represents a perfluoroalkyl group having 1 to 5 carbon atoms), a monomer having a functional group, etc. Among them, HFP is preferred.

[0101] The TFE / FAVE copolymer is preferably at least one selected from the group consisting of a copolymer consisting only of a TFE unit and a FAVE unit and the above-mentioned TFE / HFP / FAVE copolymer, and more preferably a copolymer consisting only of a TFE unit and a FAVE unit.

[0102] The melting point of the TFE / FAVE copolymer is preferably 280° C. to 322° C., more preferably 285° C. or higher, more preferably 320° C. or lower, and further preferably 315° C. or lower. The melting point can be measured using a differential scanning calorimeter [DSC].

[0103] The glass transition temperature (Tg) of the TFE / FAVE copolymer is preferably 70° C. to 110° C., more preferably 80° C. or higher, and more preferably 100° C. or lower. The glass transition temperature can be measured by dynamic viscoelasticity measurement.

[0104] TFE / HFP copolymer is a copolymer containing tetrafluoroethylene (TFE) units and hexafluoropropylene (HFP) units.

[0105] The content of the HFP unit in the TFE / HFP copolymer is preferably 0.1 to 30.0 mol %, more preferably 0.7 mol % or more, further preferably 1.4 mol % or more, and more preferably 10.0 mol % or less, based on all monomer units.

[0106] The content of the TFE unit in the TFE / HFP copolymer is preferably 70.0 to 99.9 mol %, more preferably 90.0 mol % or more, more preferably 99.3 mol % or less, and further preferably 98.6 mol %, based on all monomer units.

[0107] The TFE / HFP copolymer may also contain monomer units derived from monomers copolymerizable with TFE and HFP. In this case, the content of the monomers copolymerizable with TFE and HFP is preferably 0 to 29.9 mol%, more preferably 0.1 mol% to 5.0 mol%, and even more preferably 0.1 mol% to 1.0 mol%, relative to all monomer units of the TFE / HFP copolymer.

[0108] Examples of monomers copolymerizable with TFE and HFP include FAVE, CZ 1 Z 2 =CZ 3 (CF2) n Z 4 (Where Z 1 , Z 2 and Z 3 Same or different, means H or F, Z 4represents H, F or Cl, n represents an integer of 2 to 10) and CF2=CF-OCH2-Rf 1 (Where Rf 1 represents a perfluoroalkyl group having 1 to 5 carbon atoms), an alkyl perfluorovinyl ether derivative represented by (represents a perfluoroalkyl group having 1 to 5 carbon atoms), a monomer having a functional group, etc. Among them, FAVE is preferred.

[0109] The melting point of the TFE / HFP copolymer is preferably 200°C to 322°C, more preferably 210°C or higher, further preferably 220°C or higher, particularly preferably 240°C or higher, more preferably 320°C or lower, further preferably less than 300°C, particularly preferably 280°C or lower.

[0110] The glass transition temperature (Tg) of the TFE / HFP copolymer is preferably 60°C to 110°C, more preferably 65°C or higher, and more preferably 100°C or lower.

[0111] The fluorine-containing polymer compound may have a functional group.

[0112] The functional group is preferably at least one selected from the group consisting of a carbonyl-containing group, an amino group, a hydroxyl group, a -CF2H group, an olefin group, an epoxy group, and an isocyanate group.

[0113] The carbonyl-containing group is a group containing a carbonyl group (-C(=O)-) in its structure. Examples of the carbonyl-containing group include:

[0114] Carbonate group [-OC(=O)-OR 3 (Where R 3 is an alkyl group having 1 to 20 carbon atoms or an alkyl group having 2 to 20 carbon atoms containing an ethereal oxygen atom)],

[0115] Acyl [-C(=O)-R 3 (Where R 3 is an alkyl group having 1 to 20 carbon atoms or an alkyl group having 2 to 20 carbon atoms containing an ethereal oxygen atom)],

[0116] Haloformyl [-C(=O)X 5 , X 5 is a halogen atom],

[0117] Formyl [-C(=O)H],

[0118] Formula: -R 4 -C(=O)-R 5 (Where R 4 is a divalent organic group having 1 to 20 carbon atoms, R 5 is a monovalent organic group having 1 to 20 carbon atoms),

[0119] Formula: -OC(=O)-R 6 (Where R 6 is an alkyl group having 1 to 20 carbon atoms or an alkyl group having 2 to 20 carbon atoms containing an ethereal oxygen atom,

[0120] Carboxyl [-C(=O)OH],

[0121] Alkoxycarbonyl [-C(=O)OR 7 (Where R 7 is a monovalent organic group having 1 to 20 carbon atoms)],

[0122] Carbamoyl [-C(=O)NR 8 R 9 (Where R 8 and R 9 may be the same or different and are a hydrogen atom or a monovalent organic group having 1 to 20 carbon atoms)],

[0123] Anhydride bond [—C(═O)—OC(═O)—] and the like.

[0124] As R 3 Specific examples of R include methyl, ethyl, propyl, isopropyl, and butyl. 4 Specific examples of R include methylene, -CF2-, -C6H4-, etc. 5 Specific examples of R include methyl, ethyl, propyl, isopropyl, and butyl. 7 Specific examples of R include methyl, ethyl, propyl, isopropyl, butyl, etc. 8 and R 9 Specific examples of include a hydrogen atom, a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, and a phenyl group.

[0125] The hydroxyl group is a group represented by -OH or a group including a group represented by -OH. In the present disclosure, -OH constituting a carboxyl group is not included in the hydroxyl group. Examples of the hydroxyl group include -OH, hydroxymethyl, and hydroxyethyl.

[0126] An olefin group is a group having a carbon-carbon double bond. Examples of the olefin group include the following formulas:

[0127] -CR 10 =CR 11 R 12

[0128] (Where R 10 , R 11 and R 12The functional group may be the same or different and is represented by a hydrogen atom, a fluorine atom or a monovalent organic group having 1 to 20 carbon atoms, and is preferably at least one selected from the group consisting of -CF=CF2, -CH=CF2, -CF=CHF, -CF=CH2 and -CH=CH2.

[0129] The isocyanate group is a group represented by -N=C=O.

[0130] In addition, examples of the functional group include non-fluorinated alkyl groups or partially fluorinated alkyl groups such as a -CH3 group and a -CFH2 group.

[0131] The number of functional groups in the fluorinated polymer is relative to every 10 6 The number of carbon atoms is preferably 5 to 2000. 6 The number of functional groups is more preferably 50 or more, further preferably 100 or more, particularly preferably 200 or more, more preferably 1000 or less, further preferably 800 or less, particularly preferably 700 or less, and most preferably 500 or less.

[0132] In addition, from the viewpoint of being able to form a coating layer with excellent electrical properties, the number of functional groups of the fluorine-containing polymer compound is preferably 6 The number of carbon atoms may be less than 5, or may be 0 to 4. In particular, when the fluorine-containing polymer compound has melt processability, it is preferred that the number of functional groups is within the above numerical range.

[0133] The functional group is a functional group present at the main chain end or side chain end of the fluorinated polymer compound, and a functional group present in the main chain or in the side chain, preferably present at the main chain end. As the functional group, -CF=CF2, -CF2H, -COF, -COOH, -COOCH3, -CONH2, -OH, -CH2OH, etc. can be cited, preferably at least one selected from the group consisting of -CF2H, -COF, -COOH, -COOCH3 and -CH2OH. -COOH includes a dicarboxylic anhydride group (-CO-O-CO-) formed by two -COOH bonds.

[0134] The identification of the types of the functional groups and the measurement of the number of the functional groups can be performed using infrared spectroscopy.

[0135] The number of functional groups is specifically determined by the following method. First, the copolymer is melted at 330°C to 340°C for 30 minutes and compression molded to produce a film with a thickness of 0.20 mm to 0.25 mm. The film is analyzed by Fourier transform infrared spectroscopy to obtain an infrared absorption spectrum of the copolymer, and a differential spectrum is obtained from the background spectrum in which the functional groups are completely fluorinated and do not exist. According to the following formula (A), the number of functional groups per 1×10 6 The number of functional groups N per carbon atom.

[0136] N=I×K / t(A)

[0137] I: Absorbance

[0138] K: Correction coefficient

[0139] t: film thickness (mm)

[0140] For reference, regarding the functional groups in the present disclosure, the absorption frequency, molar absorption coefficient, and correction coefficient are shown in Table 1. The molar absorption coefficient was determined from FT-IR measurement data of a low-molecular model compound.

[0141] [Table 1]

[0142] Table 1

[0143]

[0144] It should be noted that the absorption frequencies of -CH2CF2H, -CH2COF, -CH2COOH, -CH2COOCH3, and -CH2CONH2 are several tens of kaise (cm-1) lower than the absorption frequencies of -CF2H, -COF, free -COOH, and bonded -COOH, -COOCH3, and -CONH2 shown in the table, respectively. 1 ).

[0145] Thus, for example, the functional group number of -COF refers to the absorption frequency 1883 cm-1 due to -CF2COF. 1 The number of functional groups obtained from the absorption peak at 1840 cm-1 due to -CH2COF 1 The total number of functional groups found from the absorption peak at .

[0146] The above-mentioned number of functional groups can be the total number of -CF=CF2, -CF2H, -COF, -COOH, -COOCH3, -CONH2 and -CH2OH, or the total number of -CF2H, -COF, -COOH, -COOCH3 and -CH2OH.

[0147] The functional groups are introduced into the fluorinated polymer compound, for example, by a chain transfer agent or polymerization initiator used when manufacturing the fluorinated polymer compound. For example, when an alcohol is used as a chain transfer agent or a peroxide having a -CH2OH structure is used as a polymerization initiator, -CH2OH is introduced into the main chain end of the fluorinated polymer compound. In addition, by polymerizing a monomer having a functional group, the functional group is introduced into the side chain end of the fluorinated polymer compound. The fluorinated polymer compound may contain units from a monomer having a functional group.

[0148] Examples of monomers having a functional group include cyclic hydrocarbon monomers having a dicarboxylic acid anhydride group ((-CO-O-CO-) and a polymerizable unsaturated group in the ring as described in Japanese Patent Application Laid-Open No. 2006-152234, and monomers having a functional group (f) as described in International Publication No. 2017 / 122743. Examples of monomers having a functional group include monomers having a carboxyl group (maleic acid, itaconic acid, citraconic acid, undecylenic acid, etc.); monomers having an anhydride group (itaconic anhydride, citraconic anhydride, 5-norbornene-2,3-dicarboxylic anhydride, maleic anhydride, etc.), monomers having a hydroxyl group or an epoxy group (hydroxybutyl vinyl ether, glycidyl vinyl ether, etc.), and the like.

[0149] The fluorine-containing polymer compound can be produced, for example, by appropriately mixing monomers to be its structural units and additives such as a polymerization initiator and subjecting them to conventionally known methods such as emulsion polymerization and suspension polymerization.

[0150] (Method for producing covered electric wire)

[0151] The covered electric wire of the present disclosure can be produced, for example, by the following production method:

[0152] The liquid coating composition (1) is applied to the outer periphery of the rectangular electric wire substrate to form a first layer.

[0153] The liquid coating composition (2) or the powder coating composition (2) is applied to the periphery of the first layer to form the second layer,

[0154] The fluorinated polymer compound (3) is extruded onto the outer periphery of the second layer by an extrusion molding method to form the third layer.

[0155] The method for forming a layer by applying the liquid coating composition is not particularly limited, and examples thereof include spray coating, roll coating, coating with a doctor blade, dip coating, and impregnation coating.

[0156] After applying the liquid coating composition, the obtained coating film may be dried and / or fired to form a layer. Drying may be performed by a conventionally known method, preferably at a temperature of 60° C. to 200° C. for 5 to 60 minutes. Firing may be performed by a conventionally known method, preferably at a temperature above the melting point or curing temperature of the polymer compound or fluorine-containing polymer compound for 5 to 60 minutes. Firing may be performed each time the coating composition is applied, or after the coating composition is applied multiple times to form multiple layers (coating films).

[0157] The method for forming a layer by applying the powder coating composition is not particularly limited, and examples thereof include electrostatic coating, flow dip coating, and the like.

[0158] It is also possible to form a layer by calcining the obtained coating film after applying the powder coating composition. The calcination can be carried out by a conventionally known method, preferably at a temperature above the melting point or curing temperature of the polymer compound or the fluorine-containing polymer compound for 5 to 60 minutes. The calcination can be carried out each time the coating composition is applied, or after the coating composition is applied multiple times to form multiple layers (coating films).

[0159] As a method of forming a layer by extruding a fluorinated polymer compound, an extrusion molding method is used. For example, the fluorinated polymer compound can be heated and melted using an extruder, and the molten fluorinated polymer compound can be extruded onto the second layer to form a layer.

[0160] The type of extruder is not particularly limited, and the shape of the screw of the extruder is not particularly limited. L / D24, the screw is a full-stroke screw, the compression ratio is 2.8, and the extrusion temperature conditions are: C1 under the hopper, adjust the temperature of C2, C3, C4 and the barrel in turn, and adjust the temperature of each part of the head, die, and mold. The die shape is a right-angle head, which is inserted vertically into the flat wire substrate relative to the extrusion and coated with a fluorine-containing polymer compound. Regarding the die / blade, a die / blade adjusted according to the desired shape of the flat wire substrate and the coating thickness is used. Tube dies, pressure dies, etc. can also be used separately. The cooling of the resin after extrusion coating can be controlled by considering air cooling, water cooling, insulation cooling, and the desired physical properties of the fluorine-containing polymer compound and the physical properties of the wire.

[0161] The temperature setting when extruding the fluorinated polymer compound is adjusted by considering the melt viscosity and melting point of the fluorinated polymer compound. For example, C1 is the material supply part, so the temperature at which the fluorinated polymer compound in an unmelted or semi-molten state is pushed forward is preferably 180°C to 320°C. C2, C3, and C4 are preferably capable of stably conveying the fluorinated polymer compound when molten to the die head and die head at 290°C to 420°C. When the temperature is low, the productivity deteriorates. On the other hand, when the temperature is high, it also becomes the main cause of the deterioration of the fluorinated polymer compound. The screw speed is also considered to adjust the residence time of the fluorinated polymer compound in the extruder for molding. Accordingly, the linear speed of the wire coating is adjusted to obtain a wire with a target coating thickness. Similarly, the temperature of each part of the die head, die head, and mold is also set to a temperature of 290°C to 420°C considering the shear rate of the fluorinated polymer compound. Furthermore, the flat wire substrate and the flat wire substrate coated on the inner layer are heated before entering the right-angle die head, which can improve the adhesion, so it is preferred. The temperature of the rectangular electric wire substrate can be controlled within ±50°C relative to the temperature of the coating resin at the die outlet.

[0162] The coated wire may also be subjected to heat treatment. The heat treatment may be performed after the outermost layer is formed, and may be performed before or after cooling. The temperature of the heat treatment is usually above the glass transition temperature of the fluororesin, preferably 10°C lower than the melting point, and preferably 15°C lower than the melting point of the fluororesin.

[0163] The covered electric wire disclosed in the present invention can be suitably used for, for example, LAN cables, USB cables, Lightning cables, HDMI cables, QSFP cables, aerospace electric wires, underground power transmission cables, submarine power cables, high-voltage cables, superconducting cables, packaged electric wires, automotive electric wires, wiring harnesses and electrical equipment, robot and FA electric wires, OA equipment electric wires, information equipment electric wires (optical fiber cables, LAN cables, HDMI cables, Lightning cables, audio cables, etc.), internal wiring for communication base stations, high-current internal wiring (inverters, power conditioners, battery systems, etc.), internal wiring for electronic equipment, small electronic equipment and mobile wiring, movable part wiring, internal wiring for electrical equipment, internal wiring for measuring equipment, power cables (for construction, wind power / solar power generation, etc.), cables for control and measurement wiring, cables for motors, etc.

[0164] The covered electric wire of the present invention can be wound and used as a coil. The covered electric wire and coil of the present invention can be suitably used in electric devices or electronic devices such as motors, generators, and inductors. In addition, the covered electric wire and coil of the present invention can be suitably used in electric devices or electronic devices such as vehicle-mounted motors, vehicle-mounted generators, and vehicle-mounted inductors.

[0165] Although the embodiments have been described above, it should be understood that various changes in the embodiments and details may be made without departing from the spirit and scope of the claims.

[0166] <1> According to a first aspect of the present disclosure, there is provided a covered electric wire comprising a rectangular electric wire base and a covering layer formed on an outer periphery of the rectangular electric wire base, wherein:

[0167] The coating layer comprises:

[0168] A first layer formed of a liquid coating composition (1) containing a polymer compound (1) having either or both of an amide group and an imide group;

[0169] a second layer formed of a liquid coating composition (2) comprising a polymer compound (2) having either or both of an amide group and an imide group and a fluorine-containing polymer compound (2), or a powder coating composition (2) comprising a polymer compound (2) having either or both of an amide group and an imide group and a fluorine-containing polymer compound (2); and

[0170] The third layer is formed by extrusion molding of the fluorine-containing polymer compound (3).

[0171] <2> According to a second aspect of the present disclosure, there is provided a covered electric wire according to the first aspect, wherein the polymer compound (1) or the polymer compound (2) is at least one selected from the group consisting of polyamideimide, polyetherimide, polyimide and thermoplastic polyimide.

[0172] <3> According to a third aspect of the present disclosure, there is provided the covered electric wire according to the first aspect or the second aspect, wherein the fluorinated polymer compound (2) or the fluorinated polymer compound (3) is a perfluoro polymer compound.

[0173] <4> According to a fourth aspect of the present disclosure, there is provided a covered electric wire according to any one of the first to third aspects, wherein the fluorinated polymer compound (2) or (3) has a relative dielectric constant of 2.0 to 2.2.

[0174] <5> According to a fifth aspect of the present disclosure, there is provided a covered electric wire according to any one of the first to fourth aspects, wherein the melting point of the fluorinated polymer compound (3) is 250°C to 320°C.

[0175] <6> According to a sixth aspect of the present disclosure, there is provided a covered electric wire according to any one of the first to fifth aspects, wherein the volume ratio of the polymer compound (2) to the fluorinated polymer compound (2) is 10 / 90 to 90 / 10.

[0176] <7> According to a seventh aspect of the present disclosure, there is provided a covered electric wire according to any one of the first to sixth aspects, wherein the rectangular electric wire base is formed of at least one material selected from the group consisting of copper, copper alloys, aluminum, and aluminum alloys.

[0177] <8> According to an eighth aspect of the present disclosure, there is provided a covered electric wire according to any one of the first to seventh aspects, wherein the surface roughness Sz of the rectangular electric wire base is in a range of 0.2 μm to 12 μm.

[0178] <9> According to a ninth aspect of the present disclosure, there is provided the covered electric wire according to any one of the first to eighth aspects, wherein the thickness of the covering layer is 30 μm to 500 μm, and the relative dielectric constant of the covering layer is 2.1 to 2.8.

[0179] <10> According to a tenth aspect of the present disclosure, there is provided the covered electric wire according to any one of the first to ninth aspects, wherein the thickness of the third layer is 50 μm to 300 μm.

[0180] <11> According to an eleventh aspect of the present disclosure, there is provided a covered electric wire according to any one of the first to tenth aspects, wherein a partial discharge inception voltage of the covering layer satisfies the following formula.

[0181] Partial discharge starting voltage (Vp) ≥ 7.2 × t + 880

[0182] (t: thickness of the above coating layer (μm))

[0183] <12> According to a twelfth aspect of the present disclosure, there is provided a covered electric wire according to any one of the first to eleventh aspects, wherein the fluorinated polymer compound (2) or the fluorinated polymer compound (3) is present in an amount of 10 6 Each carbon atom has 5 to 1000 functional groups.

[0184] <13> According to a 13th aspect of the present disclosure, there is provided a covered electric wire according to any one of the 1st to 11th aspects, wherein the fluorinated polymer compound (3) is present in an amount of 10 6 Each carbon atom has 0 to 4 functional groups.

[0185] <14> According to a fourteenth aspect of the present disclosure, there is provided a covered electric wire according to any one of the first to thirteenth aspects, wherein the fluorinated polymer compound (3) has a melt flow rate (MFR) of 0.1 to 100 g / 10 min.

[0186] <15> According to a fifteenth aspect of the present disclosure, there is provided a covered electric wire according to any one of the first to fourteenth aspects, wherein the viscosity of the liquid coating composition (2) is 10 cP to 10000 cP.

[0187] <16> According to a sixteenth aspect of the present disclosure, there is provided a covered electric wire according to any one of the first to fifteenth aspects, wherein the powder coating composition (2) has an average particle size of 1 μm to 100 μm.

[0188] <17> According to a 17th aspect of the present disclosure, there is provided a covered electric wire according to any one of the 1st to 16th aspects, wherein the first layer is formed on the periphery of the rectangular electric wire base material, the second layer is formed on the periphery of the first layer, and the third layer is formed on the periphery of the second layer.

[0189] <18> According to an eighteenth aspect of the present disclosure, there is provided a method for producing a covered electric wire, which is a method for producing a covered electric wire based on any one of the first aspect to the seventeenth aspect, wherein:

[0190] The liquid coating composition (1) is applied to the outer periphery of the rectangular electric wire substrate to form a first layer.

[0191] The liquid coating composition (2) or the powder coating composition (2) is applied to the periphery of the first layer to form the second layer,

[0192] The fluorinated polymer compound (3) is extruded onto the outer periphery of the second layer by an extrusion molding method to form the third layer.

[0193] <19> According to a nineteenth aspect of the present disclosure, there is provided a motor including the covered electric wire according to any one of the first to seventeenth aspects.

[0194] Example

[0195] Next, embodiments of the present disclosure will be described with reference to examples, but the present disclosure is not limited to the above examples.

[0196] Each numerical value in the examples was measured by the following method.

[0197] (Surface roughness Sz)

[0198] 8000μm measured by laser microscopy 2 Surface roughness Sz in the field of view.

[0199] (Number of functional groups)

[0200] The fluorinated polymer compound was melted at 330°C to 340°C for 30 minutes and compression molded to produce a film with a thickness of 0.20 mm to 0.25 mm. The film was scanned 40 times by a Fourier transform infrared spectrometer [FT-IR (trade name: 1760X, manufactured by PerkinElmer) and analyzed to obtain an infrared absorption spectrum, which was a differential spectrum from the background spectrum in which the functional groups were completely fluorinated and did not exist. According to the following formula (A), the absorption peak of the specific functional group appearing in the differential spectrum was used to calculate the relative amount of fluorinated polymer compound to every 10 6 The number of functional groups N per carbon atom.

[0201] N=I×K / t(A)

[0202] I: Absorbance

[0203] K: Correction coefficient

[0204] t: film thickness (mm)

[0205] For reference, regarding the functional groups in the present disclosure, the absorption frequency, molar absorption coefficient, and correction coefficient are shown in Table 2. The molar absorption coefficient was determined from FT-IR measurement data of a low-molecular model compound.

[0206] [Table 2]

[0207] Table 2

[0208]

[0209] (Viscosity)

[0210] The viscosity of the coating composition was measured using a B-type viscometer described in JIS Z8803 (BII-type viscometer manufactured by Toki Sangyo Co., Ltd.). A rotary rotor #4 was used for the measurement. The measurement temperature was set to 25°C.

[0211] (Average particle size)

[0212] The average particle size of the powder coating composition was measured using a laser diffraction / scattering particle size distribution measuring apparatus manufactured by Nikkiso Co., Ltd. The particle size of the center value (median particle size) in the volume-based particle size distribution was taken as the average particle size.

[0213] (Melt Flow Rate (MFR))

[0214] According to ASTM D1238, the mass (g / 10 minutes) of the copolymer flowing out from a nozzle having an inner diameter of 2.1 mm and a length of 8 mm at 372°C and a load of 5 kg per 10 minutes was determined using a melt flow indexer (manufactured by Yasuda Seiki Co., Ltd.).

[0215] (Melting Point)

[0216] The temperature was determined as the temperature corresponding to the maximum value in the heat of fusion curve when the temperature was increased at a rate of 10° C. / min using a differential scanning calorimeter [DSC].

[0217] (Coating thickness)

[0218] The measurement is carried out by means of a micrometer.

[0219] (Relative dielectric constant)

[0220] The relative dielectric constant (ε) of the entire coating layer was calculated from the following formula by obtaining the electrostatic capacitance using LCR HiTESTER 3522-50 manufactured by HIOKI Corporation.

[0221] C=Ca+Cb

[0222] (In the formula, C is the electrostatic charge per unit length of the coating (pf / m), which is the sum of the electrostatic capacitance Ca of the flat portion and the electrostatic capacitance Cb of the corner portion.)

[0223] Ca=(ε / ε0)×2×(L1+L2) / T

[0224] Cb=(ε / ε0)×2πε0 / Log{(r+T) / r} / r

[0225] (where ε0 is the dielectric constant of a vacuum, L1 is the length of the long side of the flat portion of the flat wire substrate, L2 is the length of the short side of the flat portion of the flat wire substrate, T is the coating thickness of the entire wire, and r is the radius of curvature of the conductor corner.)

[0226] (Partial Discharge Inception Voltage (PDIV))

[0227] The cross-sectional shapes of two covered electric wires (length 140 mm) including the long sides are overlapped with each other in a manner that there is no gap within the length range of 100 mm to prepare a test piece. Then, the insulating film of 10 mm at the end of the sample is removed, and a partial discharge measuring device (DAC-PD-7 manufactured by Soken Electric Co., Ltd.) is used to apply a 50 Hz sine wave AC voltage between the flat wire substrates of the two covered electric wires in an atmosphere of 50% relative humidity, thereby measuring. The voltage rise rate is set to 50 V / sec, the voltage drop rate is set to 50 V / sec, and the voltage holding time is set to 0 seconds. The voltage at the moment when a discharge of 10 pC or more is generated is taken as the partial discharge starting voltage.

[0228] (Bending test)

[0229] When the U-shaped coil was used and both sides at 10 mm from the base point were bent in the long axis direction by R2, the case where the coating layer did not lift or wrinkle was rated as ○, and the case where the coating layer lifted or wrinkled was rated as ×.

[0230] (Adhesion strength between substrate and coating layer)

[0231] Use AGS-JAutograph (50N) (manufactured by Shimadzu Corporation) for measurement. Cut two strips of 50 mm approximately parallel in the long axis direction, cut the film at both ends into a right angle along the short axis direction, peel off 10 mm at the end, and clamp it on the upper chuck. The conductor is fixed to the lower part in a way that the long surface direction becomes horizontal. When moving the device in the tensile direction, use a clamp that moves in a linked manner in the transverse direction according to its longitudinal movement distance, and adjust the angle so that the peeled film is always perpendicular to the conductor in the long surface direction. Measure the tensile stress when it is stretched at 100 mm / min to peel off 30 mm, and take the maximum point stress as the tightness. If the tightness is above 0.1 N / mm, it is judged to be fully tight and is recorded as ○. Less than 0.1 N / mm is recorded as ×.

[0232] Example 1

[0233] The liquid coating composition A was applied to the periphery of a copper flat wire substrate having a surface roughness Sz of 1.8 μm and fired to form the first layer. The liquid coating composition B was further applied to the periphery and fired to form the second layer. The fluorine-containing polymer compound L was further extruded from the periphery by an extrusion molding method to form the third layer. Details of the method for forming the first layer using the liquid coating composition A and the method for forming the second layer using the liquid coating composition B are described below. Various properties of the obtained covered wire were measured. The results are shown in Table 3.

[0234] Embodiments 2 to 7

[0235] A covered electric wire was obtained in the same manner as in Example 1 except that the compositions and fluorine-containing polymer compounds for forming the first layer, the second layer, and the third layer were changed as shown in Table 3. Various properties of the obtained covered electric wire were measured. The results are shown in Table 3.

[0236] Comparative Example 1

[0237] A covered electric wire was obtained in the same manner as in Example 1 except that the first layer was not formed. Various properties of the obtained covered electric wire were measured. The results are shown in Table 3.

[0238] Formation of the first layer using the liquid coating composition A:

[0239] A PAI varnish (resin component: 20% by weight) in which polyamideimide (PAI) was dissolved in 3-methoxy-N,N-dimethylpropionamide was used as the liquid coating composition A. The viscosity was 341 cP.

[0240] The liquid coating composition A was sprayed, dried at 100° C. for 15 minutes, and then fired at 230° C. for 20 minutes to obtain a coating film having a thickness of 10 μm.

[0241] Formation of the second layer using the liquid coating composition B:

[0242] A polyamideimide (PAI) varnish (resin component: 34 wt%) was put into water to precipitate PAI. The varnish was pulverized in a ball mill to obtain a PAI aqueous dispersion (solid content 20 wt%). To this was added a PTFE aqueous dispersion composition (solid content: 60 wt%, number of functional groups: 10 6 The carbon atoms are 18) and water to obtain a liquid coating composition B with PAI / PTFE=25 / 75 (volume %). The viscosity is 138 cP.

[0243] The liquid coating composition B was sprayed, dried at 100° C. for 15 minutes, and then fired at 380° C. for 20 minutes to obtain a coating film having a thickness of 19 μm.

[0244] Formation of the second layer using the liquid coating composition C:

[0245] A polyimide (PI) varnish (resin component: 29 wt%) was put into water to precipitate PI. The varnish was pulverized in a ball mill to obtain a water dispersion of PI (solid content: 20 wt%). To this was added a water dispersion composition of PTFE (solid content: 60 wt%, number of functional groups: 10 wt% per 10 6 The carbon atoms are 18) and water to obtain a liquid coating composition C with PI / PTFE=30 / 70 (volume %). The viscosity is 145 cP.

[0246] The liquid coating composition C was sprayed, dried at 100° C. for 15 minutes, and then fired at 380° C. for 20 minutes to obtain a coating film having a thickness of 21 μm.

[0247] Formation of the second layer using the liquid coating composition D:

[0248] PFA powder (TFE / PPVE copolymer, number of functional groups: 10 wt. %) was added to a polyamideimide (PAI) varnish (resin component: 34 wt. %). 6 The liquid coating composition D with PAI / PFA=25 / 75 (volume %) was prepared by mixing 3-methoxy-N,N-dimethylpropionamide with 220 carbon atoms, MFR: 27 g / 10 min, melting point: 301° C., average particle size: 24 μm. The viscosity was 367 cP.

[0249] The liquid coating composition D was sprayed, dried at 100° C. for 15 minutes, and then fired at 380° C. for 20 minutes to obtain a coating film having a thickness of 22 μm.

[0250] Formation of the second layer using the powder coating composition E:

[0251] Polyamideimide (PAI) powder (average particle size 20 μm) and PFA powder (TFE / PPVE copolymer, number of functional groups: 10 6 220 carbon atoms, MFR: 27 g / 10 min, melting point: 301° C., average particle size: 24 μm) were mixed to obtain a powder coating composition E having PAI / PFA=20 / 80 (volume %). The average particle size was 23 μm.

[0252] The powder coating composition E was electrostatically coated and fired at 380° C. for 20 minutes to obtain a coating film having a thickness of 20 μm.

[0253] Formation of the second layer using powder coating composition F:

[0254] Polyamideimide (PAI) powder (average particle size 20 μm) and FEP powder (TFE / HFP copolymer, number of functional groups: 10 6 625 carbon atoms, MFR: 38 g / 10 min, melting point: 258° C., average particle size: 41 μm) were mixed to obtain a powder coating composition F having PAI / FEP=20 / 80 (volume %). The average particle size was 26 μm.

[0255] The powder coating composition F was electrostatically coated and fired at 380° C. for 20 minutes to obtain a coating film having a thickness of 18 μm.

[0256] Formation of the third layer using the fluorinated polymer compound L:

[0257] PFA pellets (TFE / PPVE copolymer, number of functional groups: 6 As the fluorinated polymer L, a fluorinated polymer having 55 carbon atoms, MFR: 12 g / 10 min, and melting point: 311°C) was used.

[0258] Formation of the third layer using the fluorinated polymer compound M:

[0259] PFA pellets (TFE / PPVE copolymer, number of functional groups: 6 As the fluorine-containing polymer compound M, a fluorine-containing polymer compound having 169 carbon atoms, MFR: 28 g / 10 min, melting point: 305°C) was used.

[0260] Formation of the third layer using the fluorinated polymer compound N:

[0261] PFA pellets (TFE / PPVE copolymer, number of functional groups: 6808 carbon atoms, MFR: 68 g / 10 min, melting point: 299° C.) was used as fluorine-containing polymer compound N.

[0262] Formation of the third layer using the fluorinated polymer compound O:

[0263] FEP pellets (TFE / HFP copolymer, number of functional groups: 6 625 carbon atoms, MFR: 38 g / 10 min, melting point: 258° C.) was used as the fluorine-containing polymer compound O.

[0264]

Claims

1. A covered electric wire comprising a flat electric wire base material and a covering layer formed on the outer periphery of the flat electric wire base material, wherein: The coating layer comprises: A first layer formed of a liquid coating composition (1) containing a polymer compound (1) having either or both of an amide group and an imide group; a second layer formed of a liquid coating composition (2) comprising a polymer compound (2) having either or both of an amide group and an imide group and a fluorine-containing polymer compound (2), or a powder coating composition (2) comprising a polymer compound (2) having either or both of an amide group and an imide group and a fluorine-containing polymer compound (2); and The third layer is formed by extrusion molding of the fluorine-containing polymer compound (3).

2. The covered electric wire according to claim 1, wherein The polymer compound (1) or the polymer compound (2) is at least one selected from the group consisting of polyamideimide, polyetherimide, polyimide and thermoplastic polyimide.

3. The covered electric wire according to claim 1 or 2, wherein: The fluorine-containing polymer compound (2) or the fluorine-containing polymer compound (3) is a perfluorinated polymer compound.

4. The covered electric wire according to any one of claims 1 to 3, wherein The relative dielectric constant of the fluorinated polymer compound (2) or the fluorinated polymer compound (3) is 2.0 to 2.

2.

5. The covered electric wire according to any one of claims 1 to 4, wherein The melting point of the fluorine-containing polymer compound (3) is 250°C to 320°C.

6. The covered electric wire according to any one of claims 1 to 5, wherein The volume ratio of the polymer compound (2) to the fluorine-containing polymer compound (2) is 10 / 90 to 90 / 10.

7. The covered electric wire according to any one of claims 1 to 6, wherein The rectangular electric wire substrate is formed of at least one material selected from the group consisting of copper, copper alloys, aluminum, and aluminum alloys.

8. The covered electric wire according to any one of claims 1 to 7, wherein The surface roughness Sz of the rectangular electric wire substrate is in the range of 0.2 μm to 12 μm.

9. The covered electric wire according to any one of claims 1 to 8, wherein The thickness of the coating layer is 30 μm to 500 μm, and the relative dielectric constant of the coating layer is 2.1 to 2.

8.

10. The covered electric wire according to any one of claims 1 to 9, wherein The thickness of the third layer is 50 μm to 300 μm.

11. The covered electric wire according to any one of claims 1 to 10, wherein The partial discharge inception voltage of the coating layer satisfies the following formula: Partial discharge starting voltage (Vp) ≥ 7.2 × t + 880 t: thickness of the coating layer, in μm.

12. The covered electric wire according to any one of claims 1 to 11, wherein The fluorinated polymer compound (2) or the fluorinated polymer compound (3) is present in an amount of 10 6 Each carbon atom has 5 to 1000 functional groups.

13. The covered electric wire according to any one of claims 1 to 11, wherein Fluorine-containing polymer compound (3) per 10 6 Each carbon atom has 0 to 4 functional groups.

14. The covered electric wire according to any one of claims 1 to 13, wherein The melt flow rate MFR of the fluorinated polymer compound (3) is from 0.1 g / 10 min to 100 g / 10 min.

15. The covered electric wire according to any one of claims 1 to 14, wherein The viscosity of the liquid coating composition (2) is 10 cP to 10000 cP.

16. The covered electric wire according to any one of claims 1 to 15, wherein The average particle size of the powder coating composition (2) is 1 μm to 100 μm.

17. The covered electric wire according to any one of claims 1 to 16, wherein The first layer is formed on the outer periphery of the rectangular electric wire base material, the second layer is formed on the outer periphery of the first layer, and the third layer is formed on the outer periphery of the second layer.

18. A method for producing a covered electric wire, the method being for producing the covered electric wire according to any one of claims 1 to 17, wherein: The liquid coating composition (1) is applied to the outer periphery of the rectangular electric wire substrate to form a first layer, The liquid coating composition (2) or the powder coating composition (2) is applied to the periphery of the first layer to form the second layer, The fluorinated polymer compound (3) is extruded onto the outer periphery of the second layer by an extrusion molding method to form the third layer.

19. A motor comprising the covered electric wire according to any one of claims 1 to 17.

Citation Information

Patent Citations

  • Fluorine-containing copolymer and its use

    JP2006152234A

  • Electric wire and process for production thereof

    WO2011024809A1

  • Curable composition, cured product, prepreg and fiber-reinforced molded article

    WO2017122743A1